Cytopathological study of salivary gland lesion in patients at a tertiary care centre, Indore: a one-year study - Todase, Vipin; Panchonia, Ashok; Kulkarni, C. V.; Mehar, Rakesh; Shinde, Pankaj (International Journal of Research in Medical Sciences, 2017)
Background: Fine needle aspiration cytology (FNAC) is being increasingly used in the diagnosis of salivary gland lesions. However, the diagnosis is still difficult sometimes. Salivary gland lesions account for 2-6.5% of all the neoplasms of the head and neck. The objective of this study was to evaluate the diagnostic accuracy and the sensitivity and specificity of FNAC in various salivary gland lesions and their histological correlation wherever possible. Methods: A total of 123 FNACs were done on salivary gland swellings in the Department of Pathology, M.G.M. Medical College, Indore, Madhya Pradesh, India. The PAP stained cytological and H and E stained histopathological slides were studied and correlated. Results: On FNAC, slides were studied and analyzed and the following lesions were observed: Inflammatory lesion (69), Inflammatory cystic lesion (1), Pleomorphic adenoma (29), monomorphic adenoma (1), Warthin’s tumour (2), Benign Cystic lesion (4), Benign lesion (not specified) (4), Adenoid cystic carcinoma (3), Mucoepidermoid carcinoma (2), Metastatic carcinoma (3), and malignant tumour (unspecified) (5). Histopathological correlation was available in 41 cases and studied respectively. Conclusions: The overall sensitivity, specificity and the diagnostic accuracy were 90.2%, 97.6%, and 90.2%, respectively. Hence, the appropriate therapeutic management could be planned earlier. This study documents that FNAC of the salivary gland tumours is accurate, simple, rapid, inexpensive, well tolerated and harmless procedure for the patient.